Comparison of treatment outcomes of direct oral anticoagulants and heparin for patients with Takotsubo cardiomyopathy: A nationwide cohort analysis - Sadahiro Hijikata; Norihiko Inoue; Kiyohide Fushimi; Tetsuo Sasano (PLoS ONE, 2025)
Takotsubo cardiomyopathy is characterized by temporary ballooning of the left ventricle and may lead to thrombosis, necessitating anticoagulation therapy in high-risk patients. However, no previous studies have compared anticoagulation therapies for this population. We aimed to compare the clinical outcomes of patients treated with direct oral anticoagulants (DOACs) and those treated with heparin. This retrospective study included patients with Takotsubo cardiomyopathy receiving DOACs or heparin within the first 2 days of admission between April 2012 and March 2021, identified from a nationwide in-hospital database in Japan. The primary outcome was in-hospital mortality. The secondary outcomes were ischemic and bleeding events, hospitalization costs, and length of hospital stay. After adjustment with propensity score-based inverse probability weighting, the risks of outcomes were estimated using Poisson regression models. Among 4,813 patients, 530 received DOACs and 4,283 received heparin. The DOAC group was older than the heparin group (mean [standard deviation] 78.1 [9.4] vs. 74.4 [11.2] years). After covariate adjustment, in-hospital mortality (4.0% vs. 3.8%; p = 0.87), ischemic events (1.1% vs. 2.8%; p = 0.067), and bleeding events (0.2% vs. 0.3%; p = 0.67) did not significantly differ between the DOAC and heparin groups. In contrast, the DOAC group had shorter hospital stays (median, 11 days vs. 13 days; p < 0.001) and lower total hospitalization costs ($5,181 USD vs. $6,084 USD; p = 0.003). These findings provide clinicians with valuable insights regarding the use of DOACs for patients with Takotsubo cardiomyopathy.